Selección y archivo desde una aproximación crítica a la relación entre imágenes y violencia (2020)
This paper adds to the current debate about the strategies to show violence through the analysis of “The Last Night”, photobook recently published, and that is located in the context of the Colombian armed conflict of the second half of the XXth century. Since the topic of the memory becomes remarkably important for this discussion, we start from Jacques Derrida´s approach. This author, supported by Nietzsche, summons us to elaborate further on the relationship between archive and memory, examining the role of images thereof. According to him: a) memory is signed by the principle of ruin, of pollution, of untimeliness and of spectrality; b) the archive is not innocent, nor is it guided by the alleged objectivity of aesthetic disinterest, since it involves trimming and excluding, and implies relentless tensions and interpretative processes that appeal to the imposition mechanisms of an authority. From there we proceed to rebuild the conditions of a productive dialogue with other theoretical perspectives, as that of Walter Benjamin in the way of the interpretation suggested by George Didi-Huberman, with the purpose of enriching our comprehension of the quoted document.